2003
DOI: 10.1007/bf03017798
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator premedication does not decrease respiratory adverse events in pediatric general anesthesia

Abstract: P Pu ur rp po os se e: : Upper respiratory infections (URI) presage perioperative respiratory complications, but thresholds to cancel surgery vary widely. We hypothesized that autonomically-mediated complications seen during emergence from anesthesia would be predicted by capnometry and reduced with preoperative bronchodilator administration.M Me et th ho od ds s: : Afebrile outpatient tertiary-care children (age two months to 18 yr, n = 109) without lung disease or findings, having non-cavitary, non-airway su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 39 publications
1
26
1
1
Order By: Relevance
“…Although URI is the most common reason for cancellation of surgery in pediatric patients [8], the issue of whether to proceed or postpone the procedure and how long to postpone it has been a source of debate for many years. Several studies demonstrated that most RAE in children with an active URI were manageable and an active URI was not associated with an increase in morbidity [6,9,10]. In the current study, even though one case of laryngospasm and two cases of oxygen desaturation occurred, these complications were properly managed and not related to long-term sequelae.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Although URI is the most common reason for cancellation of surgery in pediatric patients [8], the issue of whether to proceed or postpone the procedure and how long to postpone it has been a source of debate for many years. Several studies demonstrated that most RAE in children with an active URI were manageable and an active URI was not associated with an increase in morbidity [6,9,10]. In the current study, even though one case of laryngospasm and two cases of oxygen desaturation occurred, these complications were properly managed and not related to long-term sequelae.…”
Section: Discussionmentioning
confidence: 45%
“…Therefore, most cases proceed after the parents are warned of the risk. In addition, the previous studies demonstrated that even though an active URI increases the risk of RAE, most children with an active URI undergo the elective procedure safely and without increased morbidity [6,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…[7] 109 çocuk hastayla yaptıkları çalış-mada, pediatrik genel anestezi uygulamasında, bronkodilatör premedikasyonun solunumsal istenmeyen etkileri azaltmadığını göstermişler. Çalışma gruplarında bir haftadan daha kısa süre önce ÜSYE geçiren hastalar da olmasına rağmen, plasebo grubuna göre anlamlı fark bulunmamış.…”
Section: Discussionunclassified
“…This approach may be important for the patient with URI-induced airway hyperreactivity. Elwood et al [25] showed that the administration of ipratropium or albuterol preoperatively had no effect on complications in children with URIs [25]. Conversely, Kil et al [26] showed that prophylactic administration of albuterol or iptratropium reduced lung resistance following tracheal intubation compared with placebo, and Silvanus et al [27 ] showed that intubation-induced bronchospasm was reduced in patients receiving a preoperative combination of corticosteroids and salbutamol.…”
Section: Case Managementmentioning
confidence: 95%